Design and Development of an Ethanol Dehydrator Prototype Using Zeolite 3Å Molecular Sieves - Raihan Aprila; Annisa Dede Azahra; Rosalina Rosalina; Regna Tri Jayanti (G-Tech: Jurnal Teknologi Terapan, 2026)
Conventional distillation cannot surpass the ethanol-water azeotropic limit (95–96%), necessitating advanced dehydration for fuel grade ethanol (FGE) production per SNI 7390-2012 (≥99.5%). This study designed, fabricated, and evaluated a laboratory-scale ethanol dehydrator prototype featuring a novel 65° inclined horizontal adsorption column filled with 3Å zeolite molecular sieve a configuration not previously reported for ethanol dehydration. Product purity was measured using Gas Chromatography (Shimadzu GC-2010, FID). Under optimal first-run conditions, the system elevated ethanol purity from 96% to 99.79%, successfully meeting the FGE standard. Average vaporizer energy efficiency reached 42.49%, and maximum zeolite adsorption capacity was 0.1277 g water/g zeolite. The 65° inclined column design effectively minimized channeling and outperformed conventional vertical configurations, demonstrating its potential as a practical, low-infrastructure solution for community-scale bioethanol purification.